International note: Exploring differences in native and immigrant adolescents' mathematics achievement and dispositions towards mathematics in Qatar. (16th January 2015) - Areepattamannil, Shaljan; Melkonian, Michael; Khine, Myint Swe
ABSTRACT: The burgeoning immigrant population in major immigrant‐receiving countries in North America and Europe has necessitated researchers and policymakers in these countries to examine the academic success of children of immigration and the factors contributing to their academic success. However, there is sparse research on the academic trajectories of children of immigration in other continents, such as Asia. Hence, the purpose of the present study was to examine first‐ and second‐generation immigrant adolescents' mathematics achievement and dispositions towards mathematics in comparison to their native peers in one of the Middle Eastern countries in Asia, Qatar. The results of the study indicated that both first‐ and second‐generation immigrant adolescents tended to have higher mathematics achievement, intrinsic motivation to learn mathematics, instrumental motivation to learn mathematics, mathematics self‐efficacy, and mathematics self‐concept than did their native counterparts. Moreover, immigrant adolescents tended to have lower mathematics anxiety than did their native peers. The study also revealed significant differences between first‐ and second‐generation immigrant adolescents with respect to their mathematics achievement and dispositions towards mathematics.